Training in writing creative literary works to improve 21st century skills for elementary school teachers - Andarini Permata Cahyaningtyas; Pundani Eki Pratiwi; Aldina Eka Andriani; Indra Simanungkalit (Community Empowerment, 2023)
This community service activity is prompted by teachers' demand for competence in writing literary works, particularly poetry and short stories. Therefore, the objective of this community service is to enhance the writing abilities of teachers at SDN Genuksari 01 in Semarang City, focusing on poetry and short story composition. The activity is divided into two stages: preparation and implementation. These stages include delivering materials, engaging in question and answer sessions, providing assistance in literary work composition, and conducting outreach on self-publication. The positive reception of this activity is evident due to the numerous benefits it brings to participants. These include an increase in knowledge and competence in composing poetry and short stories based on their observations and experiences. Participants also learn to create poetry using simple words. The aspiration is that this knowledge won't be confined to teachers alone but will also be passed on to students, fostering a greater appreciation for engaging in literary work.